Facilitating Cross-Cultural Mentoring - Glenn A. Palmer; Dionne Rosser-Mims (Adult Education Research Conference, 2010)
Researchers have recognized several factors that are formidable forces preventing African Americans and other minorities to achieve their fullest potentials in organizations (Thomas, 1989; Hackett & Byers 1996). Studies have revealed that African American women are more disadvantaged than African American men in the career development process (Cox & Blake 1991; Cox, 1993; Palmer, 2001). While racism remains a defiant career barrier for both, African American women must deal with the added layer of sexism. Experts and scholars believe that various barriers (discrimination, prejudice, structural variables, lack of mentoring, etc.) have prevented African Americans from achieving their full potentials in the workplace (Carnevale & Stone, 1995). Studies have concluded that the lack of mentoring can have a negative impact on the career development of African Americans. Much of the mentoring that occurs in organizations tends to be on an informal basis and occurs between diverse groups within organization.